Role of Teachers’ Union in Professional Development of Teachers in the Public Universities of Nepal - Khanal, Basudev (Rupantaran: A Multidisciplinary Journal, 2021)
This paper focuses on the role of teachers' union in the professional development of teacher in the public universities of Nepal. To date no worth mentioning impression about the activities of teachers’ union in the professional development of teachers has been observed. Hence, this paper explores the affirmative role of the union in the professional development of its members. In the course of this study, in-depth interview was carried out for the collection of the data and thematic analysis was done for analysis and interpretation. The participants in this research were five leaders from different teachers’ unions and two members as beneficiaries from the union. It has been found that the teachers’ union works as a platform for sharing knowledge and skills among the teachers, and it also makes the existing teachers as well as the newly appointed teachers aware of the recent development in the field of teaching and learning in the global education ambiance. Moreover, the use of different available networks facilitates in encouraging the academic actions that eventually supports in the professional enhancement of the teachers.